Feminist Periodicals v.30, no.1 (Winter 2010) - (:unkn) unknown (University of Wisconsin System Women's Studies Librarian's Office, 2010)
Sub-title: A Current Listing of Contents. 241p. ISSN 1941-725X.
Table of contents periodical
Keywords: Women's Studies; Periodicals; Tables of Contents; Resources; Gender; Feminism; Lesbian Periodicals--Index; Women's Periodicals--Index